2005
DOI: 10.1074/jbc.m413081200
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the PDGFR-β Gene Affects Key Fibroblast Functions Important for Wound Healing

Abstract: Platelet-derived growth factors (PDGFs) 1 are major mitogens for connective tissue cells that are involved in diverse biological processes including physiological development, tissue repair, tumorigenesis, and atherosclerosis (1). PDGF family members, PDGF-A, -B, -C, and -D, are assembled as disulfide-linked homo-or heterodimers and exert their activity by binding to and activating specific high affinity cell surface receptors. Two receptor subtypes with protein-tyrosine kinase activity have been identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 37 publications
7
98
1
1
Order By: Relevance
“…Previously, we showed that PDGF but not LPA or FBS stimulates human fibroblast migration in nested collagen matrices . Serum frequently has been used as an agonist to study cell migration, and PDGF is believed to be the major promigratory factor for fibroblasts in serum (Li et al, 2004;Gao et al, 2005). However, serum also contains the lipid growth factor sphingosine-1-phosphate (Eichholtz et al, 1993;Yatomi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that PDGF but not LPA or FBS stimulates human fibroblast migration in nested collagen matrices . Serum frequently has been used as an agonist to study cell migration, and PDGF is believed to be the major promigratory factor for fibroblasts in serum (Li et al, 2004;Gao et al, 2005). However, serum also contains the lipid growth factor sphingosine-1-phosphate (Eichholtz et al, 1993;Yatomi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To further define the receptor signaling pathways that mediate PDGF-BB-recruited CAFs and CAMFs, we genetically deleted PDGFRβ in mice in a conditional knockout model (29,30). Deletion of PDGFRβ significantly decreased vascular pericyte coverage in PDGF-BBnegative control vector tumors, supporting the vascular function of PDGF-BB in recruitment of pericytes to angiogenic vessels ( Fig.…”
Section: Genetic Deletion Of Pdgfrβ In Mice Attenuates Pdgf-bb-recruitedmentioning
confidence: 99%
“…3 Cultured dermal fibroblasts lacking functional PDGFR-␤ show impaired mitosis and complete inhibition of migration with decreased phosphorylation of Akt, extracellular signal-regulated kinase (ERK)1/2, and c-Jun NH 2 -terminal protein kinase (JNK), but not p38 mitogenactivated protein kinase (MAPK). 15 The addition of exogenous PDGF-BB increases fibroblast proliferation and migration into the wound, indirectly leading to both increased extracellular matrix production and wound tensile strength. 16,17 In addition, overexpression of PDGFR-␤ within lesional connective tissue compartments has been noted in several fibrotic disorders including systemic sclerosis 18 and dermal scarring.…”
mentioning
confidence: 99%